Il sistema cartografico del Catasto quale strumento di supporto alla gestione delle emergenze - Ferrante, Flavio Celestino; Ambrosiano, Maurizio (GEOmedia, 2016)
The mapping system of Italian Cadastre as a support tool for emergency management. The Italian Cadastre, incorporated in the Agenzia delle Entrate from 1 December 2012, is today a complex and dynamic reality, characterized by the massive use of advanced technologies that allow to remotely communicate with external users through web platforms. Today is higher the degree of computerization achieved in managing such data, but especially in the selection and development of innovative technological solutions that allow real-time updating of cartographic and census archives in respect of the total transparency of administrative procedures.